2008
DOI: 10.1007/s00280-008-0841-4
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics meta-analysis of plitidepsin (Aplidin®) in cancer subjects

Abstract: The integration of phase I/II pharmacokinetic data demonstrated plitidepsin linear elimination from plasma, dose-proportionality up to 8.0 mg/m(2), and time-independent pharmacokinetics. The distribution to red blood cells can be considered linear at doses lower than 5 mg/m(2) administered as 3-h or longer infusion. No clinically relevant covariates were identified as predictors of plitidepsin pharmacokinetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…In plasma and whole blood, mean half-lives ranged from 21 to 44 hours. Plitidepsin is widely distributed, with apparent volumes of distribution at steady state ( V ss) ranging from 500 to 1,350 L. Approximately 97.3% of the human plasma protein was bound 26. Mean clearance values in plasma range from 45 to 49 L/h.…”
Section: Designmentioning
confidence: 99%
See 2 more Smart Citations
“…In plasma and whole blood, mean half-lives ranged from 21 to 44 hours. Plitidepsin is widely distributed, with apparent volumes of distribution at steady state ( V ss) ranging from 500 to 1,350 L. Approximately 97.3% of the human plasma protein was bound 26. Mean clearance values in plasma range from 45 to 49 L/h.…”
Section: Designmentioning
confidence: 99%
“…Plitidepsin was evaluated as a single agent in six trials (one of them in children), in which it consistently showed limited efficacy (Table 2). 26–34 Overall, in 252 patients, two confirmed partial responses (PRs) and four unconfirmed PRs were found from all Phase I studies of plitidepsin. Clinical benefit, defined as stable disease (SD) lasting more than 3 months (time to progression [TTP] >3 months) was observed in 30 adult patients (range of clinical benefit, 3.0–9.7 months) and six children (range, 3.5–13.0 months).…”
Section: Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The data revealed that breast, melanoma, and non-small-cell lung cancer appear to be sensitive to low concentrations of Aplidine [27], [28]. Aplidin has entered into phase II clinical trials in Europe and Canada for the treatment of renal, head and neck, and medullary thyroid tumors [29]. Didemnin B, a branched N -methylated cyclic peptolide, was originally isolated from the Trididemnum genus of marine tunicates.…”
Section: Resultsmentioning
confidence: 99%
“…This same model was defined for plitidepsin in a population PK meta-analysis of data from 283 patients with advanced solid tumors who received the drug as monotherapy at doses ranging from 0.13 to 8.0 mg/m 2 and at different schedules, one of which was the one evaluated in the present study. 26 In conclusion, single-agent plitidepsin has shown antitumor activity and a tolerable safety profile in patients with relapsed/refractory non-cutaneous PTCL. These results therefore support the conduct of further clinical trials to evaluate plitidepsin-containing combined therapies in this disease setting.…”
Section: Studymentioning
confidence: 99%